The future of branding within the pharmaceutical industry - Moss, Giles D. (Henry Stewart Talks, 2009)
How has consumer branding developed and what are the differences between it and pharmaceutical branding, Established consumer brand architecture and how to apply it to pharmaceuticals, Kapferer and Aaker theory and how it can be applied, The future for branding within pharmaceuticals